Axillary response according to neoadjuvant single or dual human epidermal growth factor receptor 2 (HER2) blockade in clinically node‐positive, HER2‐positive breast cancer. Issue 8 (8th July 2021) - Cha, Chihwan; Ahn, Sung Gwe; Kim, Dooreh; Lee, Janghee; Park, Soeun; Bae, Soong June; Kim, Jee Ye; Park, Hyung Seok; Park, Seho; Kim, Seung Il; Park, Byeong‐Woo; Jeong, Joon
Abstract: Incorporating dual human epidermal growth factor receptor 2 (HER2) blockade into neoadjuvant systemic therapy (NST) led to higher response in patients with HER2‐positive breast cancer. However, axillary response to treatment regimens, including single or dual HER2 blockade, in patients with clinically node‐positive breast cancer remains uncertain. Our study aimed to examine the pathologic axillary response according to the type of NST, that is, single or dual HER2 blockade. In our study, 546 patients with clinically node‐positive, HER2‐positive breast cancer who received NST followed by axillary surgery were retrospectively selected and divided into three groups: chemotherapy alone, chemotherapy + trastuzumab and chemotherapy + trastuzumab with pertuzumab. The primary outcome was the axillary pathologic complete response (pCR). Among 471 patients undergoing axillary lymph node dissection, the axillary pCR rates were 43.5%, 74.5% and 68.8% in patients who received chemotherapy alone, chemotherapy + trastuzumab and chemotherapy + trastuzumab with pertuzumab, respectively. There was no difference in axillary pCR rates between patients who received single or dual HER2 blockade ( P  = .379). Among patients receiving chemotherapy + trastuzumab, patients without breast pCR had the greatest risk for residual axillary metastases (relative risk, 9.8; 95% confidence interval, 3.2‐14.9; P  < .0001). In conclusion, adding trastuzumab to chemotherapy increased the axillary pCR rate in patients with clinically node‐positive, HER2‐positive breast cancer; furthermore, dual HER2‐blockade with trastuzumab and pertuzumab did not elevate the axillary response compared with trastuzumab alone. Breast pCR could be a strong predictor for axillary pCR in clinically node‐positive patients treated with HER2‐targeting therapy. Abstract : What's new? Dual blockade of the human epidermal growth factor receptor 2 (HER2) with trastuzumab and pertuzumab is the preferred option for neoadjuvant systemic therapy (NST) against node‐positive, HER2‐positive breast cancer. Whether this approach effectively improves pathologic complete response (pCR), however, remains unclear. Here, comparison of pCR for single or dual HER2 blockade shows that trastuzumab effectively increases axillary pCR rate in clinically node‐positive, HER2‐positive breast cancer. The addition of pertuzumab to trastuzumab did not further elevate pCR rate. The findings are relevant to decisions regarding axillary surgery in breast cancer patients with pCR after NST with HER2 targeted agents.